Smart agricultural services using deep learning, big data, and IoT - Gupta, Amit Kumar 1981-; Goyal, Dinesh 1976-; Singh, Vijendra; Sharma, Harish (IGI Global, 2021)
"This book explores the application of deep learning, big data, IoT in agricultural services"--